The Mediating Role of Financial Management in the Relationship Between Financial Literacy, Income, Lifestyle, and Investment Decisions - Ida Royani; Yusuf Ayuba (Media Ekonomi dan Manajemen, 2026)
This study examines the role of financial management as a mediating variable in the relationship between financial literacy, income, lifestyle, and investment decisions. Grounded in financial literacy theory, personal financial management theory, and behavioral finance, the research proposes and empirically tests a conceptual model using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected from all 155 employees of the Smart City & Community Innovation Center (SCCIC) using a structured questionnaire measured on a five-point Likert scale. The results reveal that financial literacy and income do not have a direct effect on investment decisions; however, both variables significantly influence financial management. Financial management, in turn, has a very strong and significant effect on investment decisions and fully mediates the relationships between financial literacy and investment decisions, as well as between income and investment decisions. Conversely, lifestyle shows no significant direct or indirect effect on either financial management or investment decisions. The model demonstrates strong explanatory power, with an R² value of 0.924 for investment decisions and a Goodness of Fit (GOF) index of 0.571. These findings highlight financial management as the key mechanism through which financial knowledge and financial resources are transformed into effective investment behavior. The study contributes to the literature by emphasizing the central role of financial management in investment decision-making within a professional organizational context and offers practical implications for financial education and organizational financial capability development.